Insurance Company Financial Performance Analysis - Rasyid, Abdul (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
This study intends to examine the financial performance of insurance companies listed on the Indonesia Stock Exchange (IDX) between 2016 and 2019. This study employs the liquidity ratio, the profitability ratio, and the solvency ratio as indicators of financial performance. The sample comprises of thirteen insurance companies that are listed on the IDX and go public. The results revealed multiple findings. First, the liquidity ratio, which consists of the current ratio and the fast ratio, demonstrates fluctuations, particularly in the calculation of the current ratio. The maximum value for insurance companies with the AHAP code is 772 percent, which is included in the excellent criteria. In contrast, the insurance company with the code AMAG has the lowest value, 2%, which falls under the unfavorable criteria. The fast ratio also demonstrates positive results, with insurance companies having values greater than 1, indicating the availability of current assets to cover liabilities. The second variable is the solvency ratio, which comprises the total debt to equity ratio and the total debt to asset ratio. The insurance companies with the ASDM code have the highest total debt to equity ratio, which is 50%, indicating a solid equity-based return rate. Meanwhile, insurance companies with the AHAP code have the lowest value, 2%, indicating a weak equity-based return rate. The total debt to asset ratio is unfavorable, with insurance companies with the ASDM code having the highest value (83%) and insurance companies with the AHAP code having the lowest value (4%). Thirdly, return on assets (ROA) is used to compute the profitability ratio. ROA also fluctuates. Insurance companies with the AHAP code have the highest value, 5403%, which demonstrates the company's ability to generate exceptional returns on total assets. In contrast, insurance companies with the codes ABDA, AHAP, and AMAG have the lowest value, 6%, indicating a healthy rate of return on profits based on total assets.